A Major Shell Protein of 1, 2‐Propanediol Utilization Microcompartment Conserves the Activity of Its Signature Enzyme at Higher Temperatures. (14th March 2022) - Kumar, Gaurav; Bari, Naimat K.; Hazra, Jagadish P.; Sinha, Sharmistha
Abstract: A classic example of an all‐protein natural nano‐bioreactor, the bacterial microcompartment is a prokaryotic organelle that confines enzymes in a small volume enveloped by an outer protein shell. These protein compartments metabolize specific organic molecules, allowing bacteria to survive in restricted nutrient environments. In this work, 1, 2‐propanediol utilization microcompartment (PduMCP) was used as a model to study the effect of molecular confinement on the stability and catalytic activity of native enzymes in the microcompartment. A combination of enzyme assays, spectroscopic techniques, binding assays, and computational analysis were used to evaluate the impact of the major shell protein PduBB′ on the stability and activity of PduMCP′s signature enzyme, dioldehydratase PduCDE. While free PduCDE shows ∼45 % reduction in its optimum activity (activity at 37 °C) when exposed to a temperature of 45 °C, it retains similar activity up to 50 °C when encapsulated within PduMCP. PduBB′, a major component of the outer shell of PduMCP, preserves the catalytic efficiency of PduCDE under thermal stress and prevents temperature‐induced unfolding and aggregation of PduCDE in vitro . We observed that while both PduB and PduB′ interact with the enzyme with micromolar affinity, only the PduBB′ combination influences its activity and stability, highlighting the importance of the unique PduBB′ combination in the functioning of PduMCP. Abstract : Chaperon‐like behavior of the shell protein PduBB' towards the native enzyme PduCDE was studied. The shell protein PduBB' was found to interact with the enzyme PduCDE and protect it from temperature‐induced denaturation. It also preserved its catalytic activity during thermal stress.